Sources of term creation in modern Russian vocational education - E. . Esenina (Высшее образование в России)
The article dwells upon a problem of term creation in publications devoted to modern vocational education. The practice of using such terms as competence and competency is an evidence of an absence of the their proper conceptual comprehension or of terminological substitution.